Analisis Proses Pembuatan CAM 2SX Pada PT. XYZ - Ahmad Rafi Muzakki; Marno; Viktor Naubnome (Jurnal Serambi Engineering, 2024)
This research investigates the CAM 2SX production process at PT. XYZ, a manufacturing company that uses advanced technology to produce precision components. The process starts from initial design using CAD software to mass production using a press machine. The steps include material selection, molding and installation, as well as sample testing to ensure the accuracy and quality of the final product. This analysis emphasizes the importance of CNC, EDM and Wirecut techniques to achieve tight tolerances and production efficiency. This research provides a comprehensive overview of the production strategy used by PT. XYZ to meet market demand with high quality standards and optimal efficiency